Identification of the factors that affect clinical teaching and potential strategies to overcome them: A narrative review - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2023)
Clinical teaching does not limit to teaching alone, rather it actually deals with the process wherein students are supported in their learning process while interacting with real patients during clinical settings. The purpose of the current review was to explore the factors that impact clinical teaching and then propose the potential recommendations to overcome them. An extensive search of all materials related to the topic was carried out on the PubMed and Google Scholar search engines and 39 articles were selected based on their suitability with the current review objectives and analyzed. Keywords used in the search include clinical teaching, patient, student, and teacher in the title alone only. Clinical teaching is affected by a wide range of teacher-related, student-related, and patient-related factors, and as medical educators, we are aware of these factors so that we can minimize their impact to enhance the effectiveness of clinical teaching, thereby augmenting learning among medical students. Most of the identified factors that can influence clinical teaching can be taken care of in one or another way, if we strengthen the domain of the faculty development program. The shortage of patients, this concern can be managed by either adoption of standardized patients or by ensuring clinical teaching in outpatient department settings. To conclude, clinical teaching is an important aspect of the making of a competent medical graduate. However, the effectiveness of such sessions depends immensely on the stakeholders that are involved in the process. It is the need of the hour to identify the prevailing factors and then plan for corrective measures to neutralize the impact of such factors and also simultaneously enhance learning among students.